2020
DOI: 10.1111/eva.13067
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of Integrated Pest Management (IPM) in the light of evolution

Abstract: Integrated Pest Management (IPM) is a holistic approach to combat pests (including herbivores, pathogens, and weeds) using a combination of preventive and curative actions, and only applying synthetic pesticides when there is an urgent need. Just as the recent recognition that an evolutionary perspective is useful in medicine to understand and predict interactions between hosts, diseases, and medical treatments, we argue that it is crucial to integrate an evolutionary framework in IPM to develop efficient and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(38 citation statements)
references
References 150 publications
0
36
0
2
Order By: Relevance
“…Nevertheless, despite the incentives introduced in many countries to reduce pesticide use and the transition to organic farming (e.g. Denmark, France, Germany, Spain, the Netherlands, the United Kingdom), there is no spectacular reduction in their use (Jørgensen et al 2019 ; Chèze et al 2020 ). The analyses performed by Hedlund et al ( 2020 ) show the links between economic development and pesticide consumption over time, without reducing their use at higher levels of economic development.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, despite the incentives introduced in many countries to reduce pesticide use and the transition to organic farming (e.g. Denmark, France, Germany, Spain, the Netherlands, the United Kingdom), there is no spectacular reduction in their use (Jørgensen et al 2019 ; Chèze et al 2020 ). The analyses performed by Hedlund et al ( 2020 ) show the links between economic development and pesticide consumption over time, without reducing their use at higher levels of economic development.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, host resistance is an environment-friendly approach to manage plant diseases, but the rapid evolution of effector genes empowers plant pathogen propensity to quickly escape host defense systems, greatly threatening agricultural and ecological sustainability. To achieve sustainable plant disease management, adaptive disease management programs based on the principles of evolutionary ecology (Zhan et al, 2014(Zhan et al, , 2015, such as through spatiotemporal deployment of resistance genes (Zhan et al, 2002;Yang et al, 2019) and other available pathogen mitigation arsenals (Karlsson Green et al, 2020), are necessary. This is particularly important in the current era of climate change, such as global warming, which not only exerts eminent and short-term influences on the epidemics of plant diseases but also produces last, long-term impacts on the evolution of plant pathogens (Zhan and McDonald, 2011;Yang et al, 2016;Wu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The results also indicate that there is a large variation in crop losses due to specific P&A, which is in agreement with the findings of Savary et al (2019), but a rather low variation in yield losses according to pathogen types (e.g., fungi, bacteria). P&A are mainly controlled through the intensive use of pesticides in combination with the cultivation of GM crops, which may cause negative effects for human health, such as acute and chronic intoxication (Pignati et al, 2017) and biodiversity loss, as well as the development of pest resistance to pesticides (Karlsson Green et al, 2020). One alternative, holistic approach to combating pests is integrated pest management (IPM), which combines preventive and curative methods, and only applies chemical pesticides when there is an urgent need (Karlsson Green et al, 2020).…”
Section: Reducing Yield Losses To Pests and Diseasesmentioning
confidence: 99%
“…P&A are mainly controlled through the intensive use of pesticides in combination with the cultivation of GM crops, which may cause negative effects for human health, such as acute and chronic intoxication (Pignati et al, 2017) and biodiversity loss, as well as the development of pest resistance to pesticides (Karlsson Green et al, 2020). One alternative, holistic approach to combating pests is integrated pest management (IPM), which combines preventive and curative methods, and only applies chemical pesticides when there is an urgent need (Karlsson Green et al, 2020). A field experiment jointly established by the Embrapa and Aprosoja in MT to test the efficacy of IPM demonstrated that areas managed using IPM measures produced the same yield as areas with conventional management, but used approximately 50% less insecticide (Bueno et al, 2020).…”
Section: Reducing Yield Losses To Pests and Diseasesmentioning
confidence: 99%